The Urgency of Local Culture-Based Basic Education Purwokerto - Darojah, Rani (Universitas Trunojoyo Madura, 2022)
This study aims to analyze the need for locally charged education to improve the quality of education in the Purwokerto area. This research is a qualitative research where data sources were obtained through Focus Group Discussions (FGD) involving 25 education practitioners. as well as through a questionnaire given to 250 users, namely grade 1-6 elementary school students who were randomly selected in the Purwokerto area. The results of this study were obtained in the form of a strategic plan for Purwokerto local culture-based education, namely through equity and expansion of access to Purwokerto culture-based education, improving quality, relevance and competitiveness rooted in regional culture, strengthening accountability governance and public image as supporting elements. The conclusion of this research is in the form of recommendation considerations for education containing local wisdom, including equity and expansion of access to learning with local Purwokerto culture to make the identity and identity of education in Purwokerto, improving quality, relevance and competitiveness through unique characteristics in the form of education with regional cultural wisdom, and strengthening governance, accountability and public image regarding education based on local culture.